Sharia Compliance Study: Implementation of Ijarah and Murabahah Contracts - Niswatun Hidayah; M. Pudail; Yeny Fitriyani (Mutanaqishah: Journal of Islamic Banking, 2025)
Purpose–The objectives of this study are to explain how BMT Atina implements ijarah and murabahah contracts, evaluate if these contracts correspond with the DSN-fatwa MUI, and investigate the difficulties and solutions BMT encounters when executing these contracts. Methodology–This study employs a descriptive qualitative approach to investigate the implementation of ijarah (lease) and murabahah (sale with a profit margin) agreements, and to evaluate whether their execution complies with Sharia principles, as per the fatwa published by the DSN-MUI. Findings–Fatwa DSN-MUI No. 112/2017 implemented the ijarah and murabahah contracts at BMT Atina by clearly and honestly negotiating the rental object, term, and payment amount (ujrah). Buying the products initially and then selling them to consumers at an agreed price, including a profit margin, is clearly and openly permitted by Fatwa DSN-MUI Fatwa No. 04/2000. Implications – The findings may provide a model for other BMTs or Sharia-compliant financial companies seeking to enhance their funding options in line with Sharia principles while maintaining effectiveness. Originality – This study has original worth because it centres on a particular case study of one BMT in the Banyubiru area that has not been thoroughly explored. Simultaneously, it analyzes two important Sharia financing agreements: ijarah and murabahah. It entails interviews with several stakeholders (managers and consumers) for a more thorough viewpoint.